On asymptotic statistical equivalence of order ? of generalised difference sequences - Et, Mikail; Cinar, Muhammed; Karakas, Murat (Maejo Univ, 2014)
We introduce and examine the concepts of Delta(m)(uv) (lambda)-asymptotic statistical equivalence of order alpha, and strong Delta(m)(uv) (lambda) asymptotic equivalence of order. of sequences. Also, we give some relations connected to these concepts.
Keywords: asymptotic equivalence; difference sequences; statistical convergence